Large scale, selective dispersion of long single-walled carbon nanotubes with high photoluminescence quantum yield by shear force mixing - Graf, Arko; Zakharko, Yuriy; Schießl, Stefan Patrick; Backes, Claudia; Pfohl, Moritz; Flavel, Benjamin S.; Zaumseil, Jana (Carbon, 2016)
Selective dispersion of semiconducting single-walled carbon nanotube (SWCNTs) with conjugated polymers typically involves harsh sonication methods that damage and shorten the nanotubes. Here, we use simple high speed shear force mixing (SFM) to disperse nearly monochiral (6,5) SWCNTs with poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt-co-(6,6′-{2,2′-bipyridine})] (PFO-BPy) in toluene with high yield and in large volumes. This highly scalable process disperses SWCNTs of exceptional quality with an average tube length of 1.82 μm and an ensemble photoluminescence quantum yield (PLQY) of 2.3%. For the first time for SWCNTs, we describe and apply absolute PLQY measurements, without the need for any reference emitter. We directly compare values for average SWCNT length, PLQY, linewidth and Stokes shift to other dispersion methods, including bath and tip sonication, as well as other sorting methods such as gel chromatography. We find that SFM results in dispersions of longer SWCNT with higher average PLQY than any other technique, thus making it an ideal method for sorting large amounts of long, high quality and purely semiconducting SWCNTs.
Gesehen am 30.07.2020